Social and pedagogical technologies of formation of future teachers’ familistic competence - Кравец, Володимир Петрович (Psychological Counseling and Psychotherapy)
The article deals with social and pedagogical technologies of formation gender and familistic competence. Structural components, ways and methods of teacher’s work in preparation of students-pedagogues to gender education and formation of the future family man are mentioned. The quality of sexual socialization and premarital preparation of students is determined by increasing of the quality of the preparation of teachers in pedagogical institutions. The author’s model of professional preparation of future teachers to sexual education and premarital preparation of secondary school students is analyzed. Psychological and pedagogical conditions of its implementation are examined. On the basis of experimental verification, the potential possibilities of the subjects, curriculum of pedagogical universities and especially special courses for increase of gender and familistic competence of student-pedagogue are substantiated.